ASSESSMENT OF DRY SEASON GARDEN EGG PRODUCTION AMONG SMALL SCALE FARMERS IN EDU LOCAL GOVERNMENT AREA OF KWARA STATE, NIGERIA - Omotesho, Olubunmi Abayomi; Muhammed-Lawal, Abdulazeez; Amolegbe, Khadijat Busola; Abubakar, Tauheed Alhaji (Journal of Agricultural Sciences (Belgrade), 2017)
The study was carried out on the assessment of dry season garden egg production among small scale farmers in Edu Local Government Area of Kwara State. The study adopted a snow balling sampling technique to sampled 120 small scale garden egg farmers. Five research questions were formulated to achieve the objectives of this research work. Descriptive statistic was used to analyze the socio- economics features of the respondents. Cost and return analysis shows that The total revenue generated from the sales of irrigated garden egg produce for a typical farmer was ₦36,596.5k while the total fixed cost (depreciated) and variable inputs cost amounted to 1279.22K to give a net farm income (NFI) ₦24,582.68k .The OLS Regression result revealed that the coefficients of farm size and household size are positive and significant at 1% and 10% levels of probability respectively. This implies that an increase in farm size by 1 ha, will increase the production of dry season garden egg by 1percent. While, the result of stochastic production frontier estimate shows that the parameters labour, fertilizer and farm size are highly significant compared to chemical which is significant at 10% level of significance. This result implies that the farmers were technically efficient in the use of labour, fertilizer, chemical and farm size. It was recommended that that government should assist the dry season farmers by channeling Niger River to divert its source of water to suite adequate water supply for irrigation farming in the study area.